Curvature in the reproductive tract alters sperm–surface interactions - Mohammad Reza Raveshi (Nature Portfolio, 2021)
The effect of fallopian tube’s curvature on sperm motion has not been studied in detail. Here, the authors use droplet microfluidics to create soft curved interfaces, revealing a dynamic switch in sperm motility from a progressive surface-aligned mode at low curvatures, to an aggressive surface-attacking mode at high curvatures.